ADJUSTMENT OF THE BPK'S AUTHORITY IN AUDITING STATE FINANCES DURING EMERGENCY SITUATIONS - Slamet Suhartono,; Muhamad Alvan, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Emergency situations such as global pandemics, natural disasters, and economic crises often compel governments to adopt fiscal measures that are both rapid and unconventional. In such conditions, the principles of transparency and accountability are frequently put to the test. Amid these dynamics, the Audit Board of the Republic of Indonesia (Badan Pemeriksa Keuangan – BPK) plays a crucial role in ensuring that state financial management remains consistent with constitutional principles and public accountability values. This article examines how the constitutional authority of BPK can be effectively exercised during states of emergency, and how public audit mechanisms can be adapted without undermining the government’s flexibility in responding to crises. The study employs a juridical-normative approach, combined with conceptual analysis and a review of recent literature (particularly from academic publications between 2022 and 2025). The findings indicate that BPK’s authority is imperative and constitutionally entrenched, and thus cannot be disregarded even under extraordinary circumstances. Nevertheless, maintaining effective public oversight requires a reformulation of audit methodologies—such as the application of interim audits, risk-based audits, and institutional synergy among BPK, internal government auditors (APIP), and national crisis management bodies. Based on the author’s personal research experience on BPK’s auditing practices during the COVID-19 pandemic, the study highlights that the primary challenge does not lie in weak legal foundations but in institutional adaptation and technological capacity. Therefore, this article recommends strengthening the legal framework for auditing during emergencies, accelerating the digitalization of public audit systems, and establishing responsive inter-agency coordination networks to ensure that the principle of public accountability remains intact even amidst crises